2021
DOI: 10.1108/gm-01-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Does gender matter? A university ecosystem, self-efficacy and entrepreneurial intention analysis in Brazilian universities

Abstract: Purpose This paper aims to enlighten existing gender differences in the linkages between university ecosystem, self-efficacy and entrepreneurial intention in a developing country. Design/methodology/approach The empirical exercise relies on Partial Least Squares Structural Equations Modeling based on data from a probabilistic sample of 467 Brazilian students of 70 universities across the country. Findings The university ecosystem positively influences self-efficacy and entrepreneurial intention. Entreprene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 64 publications
6
16
0
1
Order By: Relevance
“…First off, the findings of the study indicate that male university students have a stronger sense of entrepreneurial self-efficacy than do female university students. The findings are in line with the study by Pelegrini and Moraes (2021). Similarly, Veljkovic et al (2019) found that female students majored in MBA have lower entrepreneurial self-efficacy and entrepreneurial intentions than do male students.…”
Section: Discussion and Conclusion Theoretical Contributionssupporting
confidence: 86%
“…First off, the findings of the study indicate that male university students have a stronger sense of entrepreneurial self-efficacy than do female university students. The findings are in line with the study by Pelegrini and Moraes (2021). Similarly, Veljkovic et al (2019) found that female students majored in MBA have lower entrepreneurial self-efficacy and entrepreneurial intentions than do male students.…”
Section: Discussion and Conclusion Theoretical Contributionssupporting
confidence: 86%
“…Similarly, a high level of entrepreneurial self-efficacy encourages a student to take the risk of deciding to become an entrepreneur or to engage in entrepreneurial behavior. Results like this are shown by researchers, which stated that the higher entrepreneurial self-efficacy resulted in higher entrepreneurial intentions and behavior (Crespo et al, 2020;Jarvis, 2016;Pelegrini & Moraes, 2022;Powers et al, 2021). Similarly, the availability of substantial financial support boosts student entrepreneurial self-efficacy.…”
Section: Introductionsupporting
confidence: 58%
“…Self-efficacy is reported as a good predictor of start-up intention ( Krueger et al, 2000 ; Zakaria and Nordin, 2020 ). The application and practice of social cognition theory (SCT) in entrepreneurship research indicates that EI and success are largely influenced by ESE, while Pelegrini and de Moraes (2021) revealed that the ESE of university students in developing countries significantly positively predicted EI. Meanwhile, gender difference lies in female ESE, which has a greater impact on EI.…”
Section: Literature Reviewmentioning
confidence: 99%